A Portfolio Management Method for Process Mining-Enabled Business Process Improvement Projects - Dominik A. Fischer; Maximilian Röglinger; Laura Marcus (Business & Information Systems Engineering, 2024)
Abstract Process mining has received tremendous attention from research and industry, establishing itself as a highly sought-after technology. Despite the technological maturity of process mining solutions, which has been achieved through extensive investments in research and development, organizations still face the challenge of elusive value when systematically adopting process mining. The authors attribute this dilemma to a lack of support for scaling and managing process mining project portfolios. To address this practical need and research gap, the authors propose a method for managing portfolios of so-called process mining value cases, which are defined as process mining-enabled business process improvement projects, towards an evolutionary roadmap ( mapper ). The method is designed to support organizations identify portfolios of process mining projects that generate value by improving business processes. The method was developed through a combination of design science research and situational method engineering and comprises five activities that ~each~outline techniques, roles, and tools: strategize , identify , select , implement , and monitor . The method has been instantiated as a software prototype and iteratively evaluated for applicability and real-world fidelity by involving an expert panel of academics and practitioners. The usefulness of the artifact was substantiated through a real-world case study in a naturalistic setting.
Keywords: 330; Process mining; Business process improvement; Project selection; Portfolio management